The Making Of Advertising Industry In The Czech Lands. Beginning Of The Institutionalization Of Advertising Industry In The Czech Lands From First Half Of The 19th To The 20s Of The 20th Century - Pavlů, Dušan (Communication Today, 2025)
The first provable efforts to make a specific commercial communication in the Czech Lands go deep into history – we identify them in the development of commercial communication in the rural markets in the 11th and 12th century, in the attempt to attach distinctive marks to products – predecessors of trademarks, create advertising posters on the facades of houses, and also in the development of various street communication forms of criers and naturally in the use of the only mass medium in the 18th and 19th century – periodical press as the carrier of advertising messages – advertisements, illustrations with an advertising focus which were offering goods and services. The second half of the 19th century shows efforts to codify the industry to a certain extent through the development of terminology and attempts to define advertising in encyclopaedic dictionaries, stabilize exhibitions and fairs as the most mass medium of its time. With the development of photography and film comes the era of using these media for the benefit of the advertising message, the motoring at the beginning of the 20st century gives room to the existence of mobile advertising. The turn of the century in the Czech circumstances is rich in two publications summarizing the period opinions and codifying the terminology and philosophy of this industry. The founding of the Reklamní klub československý (the Czechoslovak Advertising Club) and its development as a professional association uniting creative professionals and advertisers represents a meaningful contribution, a real boost to the industry.